Linking research, innovation and finance for climate-resilient agropastoralists in West Africa - Wane, Abdrahmane; Bucknall Williams, Rhys; Harris, Amy (2023)
The titles in this series aim to disseminate intermediate research on the extension of climate services and climate-smart agriculture in Africa to stimulate reactions from the scientific community.